Application of Alum Fixator for Eco Print Batik Making Using a Pounding Technique in Fine Arts Learning in Junior High School - Putri Lestari; Asri Wibawa Sakti (ASEAN Journal of Science and Engineering, 2022)
Art learning activities in schools are learning that must be done in practice, but currently many art educators do not provide maximum learning for students, and free students to be creative without giving directions. So that in this study it is hoped that students can understand the importance of art practice to develop students' creativity and explore the potential in students. In addition, this study aims to provide insight to junior high school students to understand that the application of an alum fixator in the process of making eco print batik can provide a new experience in the practice of fine arts at school. The method used is using quantitative methods by making 2 sessions of distributing questions, namely pretest and posttest after distributing the material delivered through PowerPoint and videos of the eco print batik making process which are analyzed in the form of statistical diagram tables. The results of the study produced a fairly good impact on the learning process, almost the entire sample of students who joined this study understood it well and wanted to apply it one day.